Penggunaan Larutan Kalsium Klorida (CaCl2) dalam Menunda Pematangan Buah Pepaya (Carica papaya L.) - Mukarlina, Megasari Ramadani, Riza Linda, (Jurnal Protobiont, 2013)
Papaya (Carica papaya L.) spreads in tropical areas. The harvested fruit generally is ripe between 4 and 5 days, therefore to maintain the quality of the fruit delaying ripening of it is needed. One of the ways to delay ripening of fruit is using Calsium Choloride (CaCl2) solution. The research project aims to find out of the influence of CaCl2solution as material for delaying ripening papaya. The study was conducted from December 2011 to May 2012 in Biology Laboratory of Biology department in Faculty of Mathematics and Natural Science, Tanjungpura University. The research methodology used experimental factorial complete randomized design which consisted of two treatments that are concentration of CaCl2 solution (C) with five levels; 0%, 2%, 4%, 6%, 8% and soaking time with five level; 0 minutes, 15 minutes, 30 minutes, 45 minutes, and 60 minutes. The investigation covered keeping period of time (days), weight decrease (%), food color, flesh color, tenderness and food glucose level (%). The best fruit storage time was 6% concentrate and soaking time was 60 minutes, and weight decrease, food color, flesh color and food glucose level was 6% concentrate and the soaking time was 30 minutes.